Influencing Higher Education Through Field-Based Development in TN LEAD - Ernest L. Bentley; W. Hal Knight (Educational Considerations, 1989)
Practitioners are being viewed by professors as partners in the school improvement process and vice versa. (Program Approaches to Administrative Training and Development.)